Autophagy activator AA-20 improves proteostasis and extends Caenorhabditis elegans lifespan - Ee Phie Tan; Nora Lyang; Saam Doroodian; Pablo Sanz-Martinez; Jin Xu; Sviatlana Zaretski; José L. Nieto-Torres; Hiroshi Ebata; Shaun H. Y. Lim; William C. Hou; Khalyd J. Clay; Leonard Yoon; et al. (Proceedings of the National Academy of Sciences, 2025)
The degradation of cellular components through autophagy is essential for longevity and healthy aging. However, autophagy function decreases with aging, contributing to age-related diseases. In this study, we characterized a small-molecule activator of autophagy called AA-20 that enhances autophagy and lipid droplet clearance in human cells and in the nematode Caenorhabditis elegans . AA-20 reduces polyglutamine aggregation in an autophagy-dependent manner in both human cells and C. elegans , where it also promotes fitness. Consistently, we found that AA-20 extends lifespan in WT C. elegans, but not in autophagy-deficient mutants. Interestingly, our findings suggest that AA-20 acts, at least in part, through a mechanism involving the transcription factor EB, but without inhibiting the protein kinase mammalian target of rapamycin complex 1. Collectively, our results identify an autophagy activator AA-20 , which may have potential therapeutic implications for aging-related proteinopathies and lipid storage disorders.